Right ventricular hydatid cyst ruptured to pericardium - Sabzi, Feridoun (Ann Card Anaesth, 2015)
Cardiac hydatidosis is rare presentation of body hydatidosis. Incidence of cardiac involvements range from 5% to 5% of patients with hydatid disease. Most common site of hydatid cyst in heart is interventricular septum and left ventricular free wall. Right ventricular free wall involvement by cyst that ruptured to pericardial cavity is very rare presentation of hydatid cyst. Cardiac involvement may have serious consequences such as rupture to blood steam or pericardial cavity. Both the disease and its surgical treatment carry a high complication rate, including rupture leading to cardiac tamponade, anaphylaxis and also death. In the present report, a 43-year-old man with constrictive pericarditis secondary to a pericardial hydatid cyst is described.